Analisis Kelelahan Kerja dan Faktor-Faktor Penyebabnya pada Caregiver di Yayasan Galuh Kota Bekasi - Daud Cahyanto; Sariah Sariah; Ahmad Farid Umar (Jurnal Persada Husada Indonesia, 2017)
Fatigue is a condition characterized by less capacity for work and reduced efficiency for achievement, usually characterized by a tired or weak condition or feeling. Fatigue in caregiver will result in decreased service productivity in patients. This research uses qualitative design with research approach used is phenomenology. The purpose of this research is to analyze the fatigue of work and its causal factors at caregiver at Galuh Kota Bekasi Foundation. The data collection process was conducted from May to June 2017, the data was taken by conducting in-depth interview, observation, and document review on 6 (six) informants (caregiver) to know the characteristics of informant, working period, work load, work environment, activity outside Hours of work and an image of work fatigue. The results showed that work fatigue in caregiver with short working period (still new) will easily feel tired compared with caregiver with long service. This is due to differences in experience and adaptation in work. The caregiver's perceived workloads are both physically, mentally, socially and responsibly, and the risks of working large numbers of patients and vary greatly in severity of illness, especially risks in the face of recurrence of patients who can at times rage. The work environment of the caregiver is very crowded, noisy, and the hot temperature conditions make caregiver get tired quickly become less lazy spirit to move. There is only one caregiver who has additional work activities outside working hours. Most caregivers rest at home after working at the Galuh Foundation. Tiredness due to work that felt caregiver in the form of physical symptoms of pain in the back, lack of concentration, frequent dizziness and headaches.